Capsicum annuum Ornamental Pepper: FPS105/FP105, 5/2007 - Gilman, Edward; Howe, Teresa (EDIS, 2007)
This document provides an overview of ornamental peppers (Capsicum annuum), detailing their growth habits, planting requirements, and uses. Ornamental peppers are annuals or perennials in warmer climates, known for their colorful fruits that range from red, purple, yellow, orange, to white. They thrive in full sun or partial shade and require a rich, evenly moist growing medium. The document also highlights their non-invasive nature, moderate growth rate, and resistance to pests. Additionally, it covers the plant’s physical characteristics, including height, spread, leaf arrangement, and fruit features. Original publication date October 1999.